2021
DOI: 10.1371/journal.pone.0256240
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on microbial keratitis presentation patterns

Abstract: Background Microbial keratitis (MK) is the most common non-surgical ophthalmic emergency, and can rapidly progress, causing irreversible sight-loss. This study explored whether the COVID-19 (C19) national lockdown impacted upon the clinical presentation and outcomes of MK at a UK tertiary-care centre. Methods Medical records were retrospectively reviewed for all patients with presumed MK requiring corneal scrapes, presenting between 23rd March and 30th June in 2020 (Y2020), and the equivalent time windows in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Butt et al . [ 47 ] also concur that there were no significant differences in the treatment outcomes of admitted and self-medicating microbial keratitis patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Butt et al . [ 47 ] also concur that there were no significant differences in the treatment outcomes of admitted and self-medicating microbial keratitis patients.…”
Section: Discussionmentioning
confidence: 89%
“…In this case series, the central ulcers (noted in cases 1 and 2) and hypopyon (noted in case 3) could be successfully managed without admitting the patients, despite COVID-19-related constraints. Butt et al [47] also concur that there were no significant differences in the treatment outcomes of admitted and self-medicating microbial keratitis patients.…”
Section: Casementioning
confidence: 93%
“…[ 28 ] The study conducted in the UK during the first wave of COVID-19 in the year 2020 showed a decline in culture positivity rate from 55% to 49%. [ 29 ] Our study had a culture positivity rate of 28.28%. The low culture positivity rate could be attributed to delayed presentation due to nationwide lockdown, delayed examination of the samples owing to increased workload in terms of increased demand for COVID-19 polymerase chain reaction sampling of nasal and throat swabs, and prior use of antimicrobials prescribed by local practitioners.…”
Section: Discussionmentioning
confidence: 96%
“…Table 5 summarizes various comparative and noncomparative studies on microbiological and demographic profile of corneal ulcers during COVID-19. [ 29 30 31 32 33 ] The current study is the only prospective study on demographic and microbiological profile of corneal ulcers during COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it offers seven-days-a-week Eye Casualty services for adults and children with acute sight threatening eye disease. Previous data obtained from 2015–2016 [ 8 ] reported that BMEC recorded approximately 120 attendances per day with up to 112.5 admissions per year due to MK with direct costs of admission of £3681 per patient. Consequently, it is evident that complex corneal disorders can negatively impact on the NHS, economy and also on patients’ quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%